A NEW APPROACH TO THE COMBINATION THERAPY OF POLYCYSTIC OVARY SYNDROME - Semenyna, H.B.; Shatylovych, K.L.; Fartushok, T.V.; Komissarova, O.S.; Yurchyshyn, O.M. (World of Medicine and Biology, 2020)
The article presents the results of hormonal parameters and metabolic homeostasis in women with polycystic ovary syndrome (PCOS) and a treatment method developed on this basis. 67 women with PCOS (main group) and 50 healthy women (control group) were under the supervision. The results showed that in women with PCOS hormonal and metabolic disorders are significant, among which a prominent place is occupied by disorders of central regulation of ovarian function, hyperandrogenism, hypoprogesteronemia, insulin resistance on the background of impaired adrenal response to change. Taking into account the pathophysiological multifactority of PCOS and in order to avoid polypharmacy, patients with PCOS were offered a combined drug based on myo-inositol in combination with Lagerstroemia speciosa extract, vitamin D3, methyl folate and chromium. The treatment lasted for 3 months. Clinical evidence of treatment efficacy was spontaneous ovulation (25%) and positive attempts to induce ovulation in resistant patients (40%), probably due to improved ovum quality, hormonal balance, and reduced incidence of insulin resistance. As a result of treatment, 64% (43/67) of patients with PCOS had a menstrual cycle improvement. 33% (22/67) of women reported a reduction in hyperandrogenic dermopathy. No side effects were observed during treatment.